Regulatory Multidimensionality of Gas Vesicle Biogenesis in Halobacterium salinarum NRC-1 - Yao, Andrew I. (Hindawi Publishing Corporation, 2011)
It is becoming clear that the regulation of gas vesicle biogenesis in Halobacterium salinarum NRC-1 is multifaceted and appears to integrate environmental and metabolic cues at both the transcriptional and posttranscriptional levels. The mechanistic details underlying this process, however, remain unclear. In this manuscript, we quantify the contribution of light scattering made by both intracellular and released gas vesicles isolated from Halobacterium salinarum NRC-1, demonstrating that each form can lead to distinct features in growth curves determined by optical density measured at 600 nm (OD(600)). In the course of the study, we also demonstrate the sensitivity of gas vesicle accumulation in Halobacterium salinarum NRC-1 on small differences in growth conditions and reevaluate published works in the context of our results to present a hypothesis regarding the roles of the general transcription factor tbpD and the TCA cycle enzyme aconitase on the regulation of gas vesicle biogenesis.